Anti-tumor targeted drug delivery systems mediated by aminopeptidase N/CD13 - Xun Wang; Bin Wang; Qiang Zhang (Elsevier, 2011)
Aminopeptidase N (APN)/CD13 is a transmembrane glycoprotein, which is overexpressed on tumor neovascular endothelial cells and most tumor cells, where it plays an important role in tumor angiogenesis. Peptides containing the Asn-Gly-Arg (NGR) motif can specifically recognize APN/CD13 allowing them to act as tumor-homing peptides for the targeted delivery of anti-tumor drugs to tumor neovascular endothelial cells and tumor cells. This article reviews the literature and recent developments related to APN/CD13, its role in tumor growth and some anti-tumor drug delivery systems containing NGR peptides designed to target APN/CD13.